BRAVE TO SPEAK, READY TO PROTECT: BODY AWARENESS EDUCATION FOR YOUNG LEARNERS - Widowati, Lorensia Panselina; Dini, Kusuma; Utami, Yosefin Beni Purbo (LPPM Univ. Ibn Khaldun Bogor, 2025)
To reduce health risks and encourage self-defense, early adolescence is a crucial time to introduce instruction on personal body safety and good hygiene practices. An efficient platform for delivering such instruction in an age-appropriate and structured way is offered by school-based interventions. The purpose of this community service program was to increase primary school kids' understanding of and proficiency with body autonomy and Personal Hygiene and Clean Living (PHBS). Methods: 86 students ages 10–13 participated in a descriptive participatory study using a one-group pre-test–post-test design. Interactive lectures, games, simulations, demonstrations, and Q&A sessions were all part of the intervention. Direct observation of hygiene routines, random oral questioning, and pre- and post-test questionnaires were used for evaluation. Results: Understanding of private body parts, personal boundaries, and hygiene ideas improved after the intervention. Throughout the lessons, students engaged in active participation and demonstrated proper handwashing and toothbrushing procedures. Effective knowledge transfer was enhanced by high levels of enthusiasm during interactive and ice-breaking activities. In conclusion, the program successfully improved primary school pupils' short-term knowledge and practical hygiene abilities. As a long-term approach to school-based health education, integrating body-safety instruction with PHBS promotion through participatory approaches is advised.